O direito natural de Platão na República e sua positivação nas leis - Gonzaga, Alvaro Luiz Travassos de Azevedo (2011)
This thesis will study the platonic thinking under the Natural Law perspective, especially in The Republic, and its following concretization and integration in Laws. We aim to observe how the platonic doctrine does not change radically, but rather completes itself with the combination of the two mentioned works, for which we shall weave our analysis setting out from the logical temporal proposition in the platonic thinking, considering also the research of his conception of Justice in order to verify the maturity of its posture as it relates to the organization of the polis